2013
DOI: 10.1098/rsob.130048
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokines can act as intracellular modulators of commensal bacterial virulence

Abstract: Interactions between commensal pathogens and hosts are critical for disease development but the underlying mechanisms for switching between the commensal and virulent states are unknown. We show that the human pathogen Neisseria meningitidis, the leading cause of pyogenic meningitis, can modulate gene expression via uptake of host pro-inflammatory cytokines leading to increased virulence. This uptake is mediated by type IV pili (Tfp) and reliant on the PilT ATPase activity. Two Tfp subunits, PilE and PilQ, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 71 publications
2
45
2
Order By: Relevance
“…While the ability of A. actinomycetemcomitans to bind and take up cytokines has been known for some time, emHofQ is the first A. actinomycetemcomitans outer membrane protein for which it has been possible to determine the binding constant for a certain cytokine. In addition, although the HofQ homolog NmPilQ has been shown to play a role in IL-8 uptake in N. meningitides [19], no binding constants were determined in that study. A specific interaction between emHofQ and IL-8 was detected in both static (K d  = 43 nM) and dynamic (K d  = 2.4 μM) settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the ability of A. actinomycetemcomitans to bind and take up cytokines has been known for some time, emHofQ is the first A. actinomycetemcomitans outer membrane protein for which it has been possible to determine the binding constant for a certain cytokine. In addition, although the HofQ homolog NmPilQ has been shown to play a role in IL-8 uptake in N. meningitides [19], no binding constants were determined in that study. A specific interaction between emHofQ and IL-8 was detected in both static (K d  = 43 nM) and dynamic (K d  = 2.4 μM) settings.…”
Section: Discussionmentioning
confidence: 99%
“…To survive in hostile environments, bacteria must have multiple ways to cope, and in host environments, bacteria could benefit by taking advantage of the host inflammatory mediators [19,3740]. Moreover, by sequestering host cytokines, bacteria could manipulate the immune signaling pathways of the host, possibly establishing an imbalance that weakens the defense of the host against invaders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, type IV pili (T4P) have also been shown to be involved in virulence of pathogenic bacteria, including P. aeruginosa, Neisseria meningitidis, and Ralstonia solanacearum (51)(52)(53). In this study, the PilZ proteins were found to regulate sliding motility, among which PXO_00049 acts as a positive regulator, whereas both PXO_02374 and PXO_02715 function as the negative ones.…”
Section: Fig 6 Subcellular Localization Of Pilz Domain Proteins In Pxo99mentioning
confidence: 81%
“…A recent study suggests that the host-inflammatory responses affect the physiol ogy of bacteria, for example, by utilizing inflammatory mediators as transcription factors [37]. It thus seems quite reasonable that bacteria have evolved mechanisms to sense their environ ment and to respond to their surrounding by using inflammatory mediators as regulators to be able to adjust and adapt to a changing environment.…”
Section: Mechanisms Of P Gingivalis Interaction With Host Cellsmentioning
confidence: 99%